Desenvolvimento e validação de uma metodologia analítica, em CLAE-PDA, para avaliação da estabilidade do 4-nerolidilcatecol na presença de seus produtos de degradação - CARDOSO, Fabiana Fernandes de Santana e Silva (2008)
The 4-nerolidylcatechol is the main secondary metabolite of the species Pothomorphe umbellata L. Miq. with established antioxidant, anti-inflammatory and photoprotective actions. Nevertheless, after its isolation and storage, evidence of photoinstability is observed, in a way that the characterization of the factors that influence such instability become mandatory, facing the perspective of a new drug development. Therefore, the aim of this paper was to develop and validate a hromatographic methodology able to analyze the degradation kinetic of the 4-NRC, in the presence of the degradation products, using the high performance liquid chromatography coupled to a detector with photodiodes (HPLC-PDA). Our results showed that the analytical method was selective (5 μg/mL) and linear over a wide range of concentrations (5.0 to 500.0 μg/mL) indicating high intra-day (0,02 2.83%) and inter-day precision (0.59 4.89%), besides accuracy (98.46 104.88%) and ruggedness. The photolytic study showed a fast degradation of 4- nerolidylcatechol (tR = 25 min), generating a major product after a total run time of 8 min. The hydrolytic study showed high instability of the substance in alkaline medium (pH 13.00), generating a major product after a chromatographic run time of 26 min. In acid conditions (pH 1.00), the degradation of 4-NRC was slow and partial, even though after 72 hours of exposure, and under heating stress. The main product of the acid degradation was seen after 12 min. The degradation kinetics of 4-NRC in alkaline and photolytic conditions showed evidences of a 2º order profile, for both reactions. Accordingly, it may be proposed the storage of 4-NRC in neutral medium, under refrigerated conditions and also, protected from light incidence preventing degradation. In addition, it must be avoided storage in solution, mainly in alkaline conditions, once they accelerate the rate of 4-NRC degradation.